1968
DOI: 10.1126/science.159.3820.1227
|View full text |Cite
|
Sign up to set email alerts
|

Boron Isotope Effect in Superconducting Zirconium Dodecaboride

Abstract: The boron isotope effect in ZrB(12) has been determined to be T(c) infinity M(alpha), where alpha is equal to - 0.09 +/- 0.05, M is the boron mass, and T(c) is the supercondiucting transition temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

1971
1971
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 8 publications
2
11
0
Order By: Relevance
“…To emphasize the variation of ρ(T) in a superconductive state, we plot these data in the inset. The transition temperature (T c0 =6.0 K) is consistent with the previously reported values for ZrB 12 (6.03 K) [11,13] and is larger than that of ZrB 2 polycrystalline samples (5.5 K) [2]. The ZrB 12 samples demonstrate a remarkably narrow transition with ∆T=0.04 K. We believe that such narrow transition is indicator of the good quality of our samples.…”
Section: Fig2 Etching Pattern Of a Zrbsupporting
confidence: 91%
See 1 more Smart Citation
“…To emphasize the variation of ρ(T) in a superconductive state, we plot these data in the inset. The transition temperature (T c0 =6.0 K) is consistent with the previously reported values for ZrB 12 (6.03 K) [11,13] and is larger than that of ZrB 2 polycrystalline samples (5.5 K) [2]. The ZrB 12 samples demonstrate a remarkably narrow transition with ∆T=0.04 K. We believe that such narrow transition is indicator of the good quality of our samples.…”
Section: Fig2 Etching Pattern Of a Zrbsupporting
confidence: 91%
“…It was suggested [3] that the superconductivity in YB 6 and ZrB 12 (T c of 6.5-7.1 K and 6.03 K, respectively [3]) is exactly due to the effect of a cluster of light boron atoms. At the same time, a much smaller isotope effect on T c for boron in comparison with Zr isotopic substitution suggests that the boron in ZrB 12 serves as inert background for the Zr-driven superconductivity [13,14]. Clearly systematic study of ZrB 12 is needed to address the question of superconductivity in this compound.…”
Section: Introductionmentioning
confidence: 99%
“…7 Since large high-quality single crystals are available, the superconductivity in ZrB 12 and YB 6 has been object of intense research. The isotope effect in ZrB 12 for zirconium 15 ͑␤ Ϸ −0.32͒ is much larger than for boron 16 ͑␤ Ϸ −0.09͒, pointing to a large contribution of lattice modes involving Zr atoms to the electron-phonon coupling responsible for superconductivity in ZrB 12 . The same was concluded from an inversion of specific-heat and resistivity data for YB 6 ͑Ref.…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that the superconductivity in YB 6 and ZrB 12 (having highest T c of 6.5 − 7.1 K and 6.03 K, respectively [3]), might be due to the hypothetical cubic metallic boron. However, a much smaller isotope effect on T c for boron in comparison with Zr isotopic substitution suggests that the boron in ZrB 12 serves as inert background, and this is Zr that actually is critical for superconductivity [11,12], even though ZrB 12 chemically contains mainly boron.…”
Section: Introductionmentioning
confidence: 99%